EVALUATION OF REFLEXES ECONOMIC-FINANCIAL OF INCENTIVES FOR INNOVATION IN THE PUBLIC COMPANIES FINEP OF BRAZIL - Parente, Paulo Henrique Nobre; Vasconcelos, Alessandra Carvalho de; Souza, Jackline Lucas; Braga, José Maurício Lima (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
This study aims to assess the economic and financial consequences of incentives to innovate FINEP of publicly traded companies in Brazil. Is characterized as descriptive, and is based on a sample of 37 companies awarded with incentives FINEP for the period 2008 to 2012. Was found that incentives FINEP caused different effects on the financial and economic performance of companies with more favorable effect in innovative companies, when compared to non-innovative firms. The analysis of profitability ratios revealed that, unlike expected, only the asset turnover of enterprises improved after receiving the incentives for innovation.